Role of microstructures on the M1-M2 phase transition in epitaxial VO(2) thin films - Ji, Yanda (Nature Publishing Group, 2014)
Vanadium dioxide (VO(2)) with its unique sharp resistivity change at the metal-insulator transition (MIT) has been extensively considered for the near-future terahertz/infrared devices and energy harvesting systems. Controlling the epitaxial quality and microstructures of vanadium dioxide thin films and understanding the metal-insulator transition behaviors are therefore critical to novel device development. The metal-insulator transition behaviors of the epitaxial vanadium dioxide thin films deposited on Al(2)O(3) (0001) substrates were systematically studied by characterizing the temperature dependency of both Raman spectrum and Fourier transform infrared spectroscopy. Our findings on the correlation between the nucleation dynamics of intermediate monoclinic (M2) phase with microstructures will open a new avenue for the design and integration of advanced heterostructures with controllable multifunctionalities for sensing and imaging system applications.